2012
DOI: 10.1111/j.1447-0594.2012.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Mini Nutritional Assessment and functional capacity in community‐dwelling elderly in Rural Luozi, Democratic Republic of Congo

Abstract: These findings provide information that malnutrition is a serious health concern among elderly people in the city of Luozi, and shows the need for adequate nutrition and social programs for the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 30 publications
5
30
1
2
Order By: Relevance
“…Unlike other studies, in which the nutritional status was predicted by functional capacity [3,5,6], our study only showed functional capacity (IADL) to be a predictor of nutritional status in the Lao and Brau ethnic groups. ADL did not predict nutritional status in any of the three ethnic groups, most likely because most of the respondents were able to carry out important tasks, such as feeding, grooming and getting into and out of bed ( Table 2).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Unlike other studies, in which the nutritional status was predicted by functional capacity [3,5,6], our study only showed functional capacity (IADL) to be a predictor of nutritional status in the Lao and Brau ethnic groups. ADL did not predict nutritional status in any of the three ethnic groups, most likely because most of the respondents were able to carry out important tasks, such as feeding, grooming and getting into and out of bed ( Table 2).…”
Section: Discussioncontrasting
confidence: 47%
“…Especially among the elderly, personal factors, such as functional capacity, which represents an individual's capacity to perform daily activities in the physical, psychological, social and spiritual domains of life [4], are vital for good health. Studies have uncovered a relationship between nutritional status and functional capacity in the elderly [3,5,6], especially among the hospitalised elderly; however, in our study we focused on the communitydwelling elderly.…”
Section: Introductionmentioning
confidence: 91%
“…The decline in performance for each functional fitness test occurred at different rates, corroborating previous data from Brazilian 20 , American 3 , and Spanish 7 studies. This decline can be explained by the presence of major changes in biological systems [24][25][26][27] , even when physical activity behavior is present. The main object of this study was to generate and compare normative functional fitness scores.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that almost half of the adults who are hospitalized are 65 years of age or older, although those older than 65 years represent only 12.5 percent of the population [2]. Aging is associated with various physiological changes and needs, which make elderly people vulnerable to malnutrition [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Application of nutritional support based on nutritional screening results significantly reduced the incidence of complications and the length of hospital stay [5]. The prevalence of malnutrition varies considerably depending on the population studied and the criteria used for the diagnosis [3]. …”
Section: Introductionmentioning
confidence: 99%